Binding Legal Force of Supreme Court Decision over General Election Commission - Madaskolay Viktoris Dahoklory; Fifiana Wisnaeni (LAW REFORM, 2020)
Election Commission Regulation Number 26 Year 2018 established by the General Election Commission as a Follow-up to the Constitutional Court Decision Number 30 / PUU-XVI / 2018 which basically prohibits candidates for Regional Representative Council who are concurrently acting as administrators of political parties but the General Election Commission's rules are canceled by the Supreme Court based on its decision Number 65 / P / HUM / 2018. The purpose of this study is to analyze and find out whether the Supreme Court's Decision has binding legal force over the General Election Commission. The research method used is juridical-normative and qualitative analysis. The research results show that the Supreme Court Decision which nullifies legal norms in the General Election Commission Regulation still has binding legal force because in principle every judge's decision must be considered valid according to the law until there is equipment (res judicata pro veritate habetur), as well as the juridical decision of the Supreme Court immediately published in the State news, with the enactment of the Supreme Court's Decision it would naturally become the basis for the validity of the a quo Decision. The decision issued by the Supreme Court indirectly gave birth to a legal obligation for the General Election Commission, for that the General Election Commission must carry it out properly. Therefore, the Election Supervisory Body needs to oversee the election commission in carrying out the mandate of the decision.